Evidence of rapid hydrogen chloride uptake on water ice in the atmosphere of Mars - Luginin, M; Trokhimovskiy, A; Taysum, B; Fedorova, AA; Korablev, O; Olsen, KS; Montmessin, F; Lefèvre, F (Elsevier, 2024)
In 2020, hydrogen chloride (HCl) in the gas phase was discovered in the atmosphere of Mars with the Atmospheric Chemistry Suite (ACS) onboard the Trace Gas Orbiter (TGO) mission (Korablev et al., 2021). Its volume mixing ratio (VMR) shows a seasonal increase of up to 5 ppbv during the perihelion season, followed by a sudden drop to undetectable levels, contradicting modelling estimates of the HCl lifetime of several months. In the Earth's stratosphere, heterogeneous uptake of HCl onto water ice is known to be a major sink for this species. This reaction is now also considered when modelling HCl abundances in the Martian atmosphere. In this work, we use simultaneous measurements of water ice and HCl obtained by the ACS instrument to find particular structures in the vertical profiles as detached gas layers at ice-free altitudes (“ice-holes”). From these particular examples we conclude that the heterogeneous uptake of HCl onto water ice operates on Mars and is a fast mechanism regulating the HCl abundance in the atmosphere of Mars.